Analysis of Factors Affecting the Utilization of PTM Posbindu at the Jailolo Health Center, West Halmahera Regency - Tuharea, Rosmila; Yusnita, Yusnita; La Patilaiya, Hairudin; Sumaryati, Sumaryati; Amin, Sahril (Publisher Cv. Inara, 2022)
Backgroud : Posbindu PTM is a form of service that involves community participation through promotive and preventive efforst to detect and control early on the presence of PTM risk factors in an integrated manner. The purpose of this study was to determine the factors that influence the utilization of PTM Posbindu at the Jailolo Health Center, West Halmahera Regency. This type of research uses cross sectional approach with a cross sectional study. The population was 201 participants with the sampling technique using the Slovin formula,namely 134 pasticipants. Data obtained by conducting interviews using a questionnaire. Data analysis was univariate and bivariate with che square statistical test with a value of=0,05. Based oh the results of the study, it can be concluded that there is a significant relationship between knowledge p-value=0,001<alpha (?=0,05), family support p-value=0,004<alpha (?=0,05), while the unrelated is attitude p-value=1.568<alpha value (?=0.05), health worker support p-value=1.249<alpha value (?=0.05) and PTM cadre support p-value=0.941<alpha value (?=0.05) on the utilization of PTM Posbindu at the Jailolo Health Center, West Halmahera Regency. It is recommended that participants take part in PTM Posbindu activities so that they can prevent PTM disease from an early age. Health workers and PTM cadres are more active in approaching or coordinating so that participants want to visit PTM Posbindu.